2013
DOI: 10.2484/rcr.v8i3.425
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal dedifferentiated liposarcoma with osteosarcomatous dedifferentiation

Abstract: We present a case of a dedifferentiated liposarcoma with osteosarcomatous degeneration in a 46-year-old male. The mass, palpated during a routine physical exam, was analyzed with dynamic, contrast-enhanced CT and CT-guided core-needle biopsy before surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…[ 1 , 6 ] But a few cases reported that RPDDL appeared as the huge cystic degeneration or contained the osteosarcomatous components with extensive calcification. [ 14 , 18 , 19 ] Furthermore, positron emission tomography-computed tomography (PET-CT) can be performed to estimate tumor grade and to obtain information on metastases. [ 11 ] Because of its high cost, only a small number of patients, to our knowledge, agree to use it in our country.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 6 ] But a few cases reported that RPDDL appeared as the huge cystic degeneration or contained the osteosarcomatous components with extensive calcification. [ 14 , 18 , 19 ] Furthermore, positron emission tomography-computed tomography (PET-CT) can be performed to estimate tumor grade and to obtain information on metastases. [ 11 ] Because of its high cost, only a small number of patients, to our knowledge, agree to use it in our country.…”
Section: Discussionmentioning
confidence: 99%